Evaluating candidate materials for balance of plant components in SOFC: Oxidation and Cr evaporation properties. (September 2021) - Reddy, Mareddy Jayanth; Svensson, Jan-Erik; Froitzheim, Jan
Highlights: Prospective Fe- and Ni-base alloys are investigated for application in BOP components. Cr, Al-lean FeCrAl alloy, A197 forms a protective oxide layer even at 650 °C. A197 has two orders of magnitude lower chromium evaporation than AISI 441 and AISI 444 at 650 °C and 850 °C. Alloy 800H formed a protective Fe-Ni spinel layer on the top of the chromia scale when exposed at 850 °C. The oxidation behaviour of the selected alloys at 650 °C improved upon pre-oxidation. Abstract: Balance of plant (BOP) components made of metallic materials in solid oxide fuel cells are subject to high-temperature corrosion and are a significant source of volatile chromium species. Prospective Fe and Ni-base alloys, AISI 441, AISI 444, a FeCrAl alloy A197/Kanthal® EF101, alloy 600, and alloy 800H are investigated for their suitability to BOP components. Oxidation kinetics and chromium evaporation were employed to study the selected alloys at 650 °C and 850 °C for 500 h. A197 performed the best while AISI 441 and AISI 444, performed the worst. Pre-oxidation significantly improved the performance of the alloys at 650 ⁰C.